Sagot :
Answer:
Given that
third term A3 = 18 and
sixth term A6 = 486
Let’s assume that the first term is ‘a’ and the common ratio is ‘r’
As we know that An = a*r^(n-1)
so, A3 = a*r^2 ——— Eq1
and A6 = a*r^5 ——— Eq2
Now, Divide Eq2 by Eq1
A6 / A3 = a*r^5 / a*r^2
=> 486 / 18 = r^(5–2)
=> 27 = r^3
=> 3^3 = r^3
=> r = 3
Now put the value of ‘r’ in Eq1
A3 = a*r^2 = 18
=> a*(3)^2 = 18
=> a*9 = 18
=> a*9 / 9 = 18 / 9 (divide both sides by 9)
=> a = 2
Ans: First term ‘a’ = 2 and common ratio ‘r’ = 3
Step-by-step explanation:
Correct me if I'm wrong:)